Study on Heart Rate and Energy Expenditure in College Sports Training Based on Multisensor Perception - Ge Liu (Hindawi Limited, 2021)
Heart rate is one of the important indices to calculate and evaluate the intensity and quality of motion. It can scientifically and objectively reflect the intensity level of momentum and exercise in the process of exercise. It is an important index of athletic strength and physical fitness of athletes in college sports training. This paper analyzes the basic metabolic model of the human body and energy supply and demand model and constructs a scientific energy consumption test model for special sports activity. An algorithm for heart rate detection and energy consumption based on acceleration data acquisition is proposed. Therefore, it is proposed to calculate motion acceleration using bone point data obtained from a portable telephone camera sensor for special sports activity and to calculate kinetic energy consumption through detection data. A model for evaluating the proposed algorithm is also established.